ANALISIS PENILAIAN KESEHATAN KEUANGAN KOPERASI SIMPAN PINJAM (KSP) SEJAHTERA SMK MUHAMMADIYAH 2 - Zahruddin Hodsay; Zelvie Yolanda (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
The formulation of the problem in this research is how is the financial health assessment of savings and loan cooperatives in the Prosperous Vocational School Muhammadiyah 2 Palembang? The object under research is the financial statements from 2015 to 2017. The research method used is descriptive. Data collection techniques using documentation and questionnaires. Technical analysis of the data used is based on aspects of capital, the quality of productive assets, management, efficiency, liquidity, independence and growth, and the identity of the cooperative. The results showed that: (1) the average capital of 10.50 in the quite healthy category, (2) the average productive assets quality of 11.25 in the less healthy category, (3) the average management of 13.75 in the quite healthy category, (4) efficiency average 10.00 in the healthy category, (5) average liquidity 6.25 in the unhealthy category, (6) independence and growth 6.00 in the unhealthy category and (7) identity for the cooperative 4.70 in the unhealthy category . The level of health of cooperatives for 3 years (2015-2017) were 66.40, 64.45 and 62.15, respectively. Thus the average of 64.40 so that it is grouped in the category of supervision.